Pharmacological characterisation of mouse calcitonin and calcitonin receptor‐like receptors reveals differences compared with human receptors. (15th October 2021) - Garelja, Michael L.; Bower, Rebekah L.; Brimble, Margaret A.; Chand, Shanan; Harris, Paul W. R.; Jamaluddin, Muhammad Aqfan; Petersen, Jakeb; Siow, Andrew; Walker, Christopher S.; Hay, Debbie L.
Abstract : Background and Purpose: The calcitonin (CT) receptor family is complex, comprising two receptors (the CT receptor [CTR] and the CTR‐like receptor [CLR]), three accessory proteins (RAMPs) and multiple endogenous peptides. This family contains several important drug targets, including CGRP, which is targeted by migraine therapeutics. The pharmacology of this receptor family is poorly characterised in species other than rats and humans. To facilitate understanding of translational and preclinical data, we need to know the receptor pharmacology of this family in mice. Experimental Approach: Plasmids encoding mouse CLR/CTR and RAMPs were transiently transfected into Cos‐7 cells. cAMP production was measured in response to agonists in the absence or presence of antagonists. Key Results: We report the first synthesis and characterisation of mouse adrenomedullin, adrenomedullin 2 and βCGRP and of mouse CTR without or with mouse RAMPs. Receptors containing m‐CTR had subtly different pharmacology than human receptors; they were promiscuous in their pharmacology, both with and without RAMPs. Several peptides, including mouse αCGRP and mouse adrenomedullin 2, were potent agonists of the m‐CTR:m‐RAMP3 complex. Pharmacological profiles of receptors comprising m‐CLR:m‐RAMPs were generally similar to those of their human counterparts, albeit with reduced specificity. Conclusion and Implications: Mouse receptor pharmacology differed from that in humans, with mouse receptors displaying reduced discrimination between ligands. This creates challenges for interpreting which receptor may underlie an effect in preclinical models and thus translation of findings from mice to humans. It also highlights the need for new ligands to differentiate between these complexes. LINKED ARTICLES: This article is part of a themed issue on Advances in Migraine and Headache Therapy (BJP 75th Anniversary).. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v179.3/issuetoc Abstract :